POTENSI EFEKTIVITAS PENERAPAN SANKSI PIDANA ALTERNATIF SEBAGAI SOLUSI PENGURANGAN OVERCROWDING DI LEMBAGA PEMASYARAKATAN INDONESIA - Trianjani, Suci; Muhammad Hanif Arkan; Nayara Dihati; Alif Hakim Parulian Tambunan (Zhata Institut, 2024)
One of the general criminal sanctions in Indonesia is imprisonment, implemented in penitentiary as a place of rehabilitation for convicts facing significant challenges in the form of overcrowding phenomenon. This article aims to discuss the effectiveness of the application of alternative criminal sanctions to reduce overcrowding in Indonesian penitentiary and the types of alternative criminal sanctions that can be applied in Indonesia. The research method used is normative juridical with a conceptual approach in the form of analysis of secondary data from legal literature and legislation, as well as descriptive-prescriptive data presentation techniques. The results show that overcrowding in Indonesian penitentiary is not balanced with the provision of adequate facilities and infrastructure, causing many problems such as fights between residents and less than optimal health services. The conclusion of this study is that overcrowding in Indonesian penitentiary is caused by a punishment policy that still prioritizes imprisonment and an imbalance between human resources and the dense inflow of convicts. To overcome this problem, it is recommended to apply alternative criminal sanctions that are more humanist, where convicts are responsible for their actions but are given the opportunity to improve themselves through constructive mechanisms such as social work, fines, coaching, or rehabilitation programs.